Enhanced Light-Gradient Boosting Machine (GBM)-Based Artificial Intelligence-Blockchain-Based Telesurgery in Sixth Generation Communication Using Optimization Concept - Punitha S.; Preetha K. S. (Journal of Electrical and Computer Engineering)
Telesurgery and robotic surgery are two real-time mission-critical applications where Artificial Intelligence (AI) has a lot of perspective. In this work, a blockchain- and AI-powered telesurgery system for 6 G communication is suggested, which describes a transparent, safe, self-managing, and trustworthy structure having massive Ultra-Reliable Low-Latency Communication (mURLLC). The condition is categorized using AI methods like Enhanced Light GBM, whose criticality scores range from 0 to 1 (after the predicted output, the criticality score of the corresponding disease is divided into high critical, medium critical, and low critical on the basis of the scores that range from 0 to 1). Here, the parameter tuning in light GBM is performed using the Tasmanian Devil Optimization (TDO) with the consideration of attaining the fitness function and thus referred to as Enhanced Light GBM. This proposed novel Enhanced Light GBM predicts the final output based on the criticality scores. In the future, recent deep learning algorithms can be considered for drone-assisted telesurgery framework together with the consideration of hybrid optimization algorithms. The proposed Enhanced Light GBM-TDO model for the drone-oriented telesurgery framework with respect to prediction accuracy is 3.22%, 3.11%, 1.84%, 3.40%, 2.26%, and 1.15% advanced than Aayush, Habits, BATS, CSIMH, MGA, and heuristic approach, respectively.